Contracting debt and the quality of financial reporting in private firms - Paiva, I. S. (Contaduría y Administración, 2018)
This study investigates whether the quality of firms' financial reporting is influenced by the contracting of debt, using data on Portuguese private firms from 2013 to 2015. More specifically, the study uses earnings smoothing, magnitude of absolute discretionary accruals, and timeliness of disclosure as proxies for financial reporting quality. I find that private firms which contract more debt exhibit higher levels of financial reporting quality. Additionally, firms that contract larger amounts of debt and with a good financial performance tend to exhibit lower quality financial reporting. The results provide strong evidence that private firms have an interest in camouflaging their performance in the presence of higher levels of bank debt.